Are They Victims of COVID-19? The livelihood and quandaries of sex workers in the New Kuchingoro camp for internally displaced people in Abuja, Nigeria - Bamidele, Seun (Anti-Trafficking Review, 2023)
In this paper, I examine the challenges faced by sex workers in the New Kuchingoro camp for internally displaced persons (IDPs) due to the COVID-19 pandemic. Previous studies on sex workers’ activities in the camp have underscored their hardships, distress, and deprivation, as well as their general inability to cope with COVID-19. Through my research, I reveal that the government and other agencies failed to support sex workers’ struggle to adequately provide for themselves and their families. I also explore the different strategies they employed in their efforts to survive during this period of hardship, which demonstrated their resilience.